Changes in potato cultivation technology in Korça region as adaptation to climate change - Maho, Adrian; Skënderasi, Besnik; Cara, Magdalena (Italian Journal of Agronomy, 2019)
The production of agricultural crops depends on the optimisation rate of plant genetic factors, climatic and soil factors and the level of agrochemicals. These factors are in constant dynamism and also are the production of agricultural plants. Changing in climatic conditions of the area will necessitate bring changes in the genetic resources of the plants that will be cultivated as well as in the technology of cultivation. The study analyses the thermal and pluviometry performance of the Korça field, one of the areas with the best agricultural development and on this basis is experimented with the time of potato planting and the adaption to these changes. The analysis of climate variability and trends of ecological climate factors is determining for the sustainability of agricultural production. Especially the increase in temperature indicators requires adaptation to the changes in the technology of crops cultivation. The planting time, which is essentially determined by the optimum agronomic temperature, determines the entire biological cycle of the plant by directly influencing the morphologic and plant yield. Climate changes of the last decades make experimentation necessary to determine the optimal planting terms. Sustainable agricultural development determined by long-term climate change requires adaptation to these changes.